ЦИСТАТИН С В ДИАГНОСТИКЕ ХРОНИЧЕСКОЙ БОЛЕЗНИ ПОЧЕК У БОЛЬНЫХ С ХРОНИЧЕСКОЙ СЕРДЕЧНОЙ НЕДОСТАТОЧНОСТЬЮ В КЛИНИЧЕСКОЙ ПРАКТИКЕ - Т. Е. Кузнецова; Н. Ю. Боровкова (SINAPS LLC, 2014)
The article discusses the use of cystatin C as an indicator of a more sensitive marker for the diagnosis of early stages of CKD in patients with chronic heart failure (CHF). Indicator cystatin C was significantly higher in patients with CHF compared with healthy aфnd increases with worsening functional class CHF. Glomerular filtration rate by cystatin C to detect a reduction in its earliest beginning with functional class II CHF.